Semi-automated integration of domain ontologies to DSL meta-models. (2017) - Haav, Hele-Mai; Ojamaa, Andres
This paper investigates the use of ontologies for the development of Domain-Specific Languages (DSL). In Model-based Software Development (MBSD), ontologies as formal models are mostly used in the phase of domain analysis as formal representations of domain models and requirements of a system. In this paper, we extend this view by introducing a concept of a DSL meta-model ontology that is defined as consisting of system ontology of a MSDB tool linked to one or more domain ontologies and external software artefacts. According to the solution presented in this paper, the given domain ontologies are semi-automatically integrated into a DSL meta-model using a set of transformations between constructs of ontology modelling language OWL and a modelling language used for representing DSL meta-models. This approach enables a dynamic semantic composition of a DSL meta-model and is prototypically implemented in Java as an extension to the DSL development tool CoCoViLa.